Optical subcarrier multiplexed system with tandem SSB transmission - Ahamad Yazeer Zeinudeen (2011)
This Project aims to design an Optical Tandem Single Side Band transmission system to transmit two data channels simultaneously. Single side Band Sub carrier multiplexed transmission systems have been popular due to attractive features like bandwidth efficiency and less dispersion penalty. The designed transmission scheme was simulated in the simulation software Optisystem. Two different data channels generated by Pseudo Random Bit Sequence Generators have been used in this experiment. And the two channels undergo a Quadrature amplitude modulation in the electrical domain prior to optical modulation.The two signals which made to be out of phase 900 each other has fed to an LiNbO3Dual Electrode Mach Zehnder Modulator (DE-MZM) for external modulation. Apart from optical modulation another main feature of the De-MZM is that cancels one side band of each signal in Channel A and Channel B. Finally the optically modulated signal will only consist of the optical carrier and one side band from the each of the signal. Transmission has been simulated in different fiber lengths and signal is received at a photo detector goes through quadrature demodulation in order to recover the two signal. Eye diagrams and Bit Error Rate measurements are used to assess the performance of the system.